Gambaran Kekuatan Karakter Perantau Etnis Madura yang Sukses - Masluhah Masluhah; Suryani Suryani (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2022)
This study aims to describe the strength of the character of the Madurese ethnic nomads and the factors that trigger the emergence of these character strengths. This research is a type of qualitative research with a phenomenological approach. The participants were collected using purposive sampling technique with a total of 4 Madurese. Data collection techniques were in-depth interviews, documentation, and audiovisual. The interview guide is based on the aspects and indicators of each virtue of the character strength variable. The results of the study show that there is a typology of character strength possessed by successful Madurese ethnic immigrants, including: creativity, open-mindedness, love of learning, courage, love, justice and equality, spirituality, morals or adab, humility, and self-regulation. In addition, character strength is also triggered by several factors such as culture, social environment, past experiences, and economic factors.